2009
DOI: 10.3892/ijo_00000396
|View full text |Cite
|
Sign up to set email alerts
|

In vitro- and in vivo-targeted tumor lysis by an MMP2 cleavable melittin-LAP fusion protein

Abstract: Abstract. Chemotherapy is one of the main treatment options for cancer, but the effectiveness of chemotherapeutic drugs is severely limited due to their systemic toxicity. Therefore, the need for a more targeted approach in tumor treatment is obvious. A tumor-activated agent would decrease systemic toxicity as well as increase the efficacy of the treatment. It has previously been shown that the latency of pro-TGF-ß is conferred by dimerization of two latency-associated peptides (LAP) that form a protective shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Consistent with this, Yu et al reported introduction of the full-length complementary DNA (cDNA) of human telomerase gene hTERT into a telomerase-negative osteosarcoma cell line U2OS (hTERT/U2OS) increased invasive ability of cells. As expected, telomere length in hTERT/U2OS cells was longer than that in vector control or un-transfected U2OS cells (Yu et al, 2009). …”
Section: Telomeres Telomerase and Cancer Spread (Metastasis)supporting
confidence: 68%
“…Consistent with this, Yu et al reported introduction of the full-length complementary DNA (cDNA) of human telomerase gene hTERT into a telomerase-negative osteosarcoma cell line U2OS (hTERT/U2OS) increased invasive ability of cells. As expected, telomere length in hTERT/U2OS cells was longer than that in vector control or un-transfected U2OS cells (Yu et al, 2009). …”
Section: Telomeres Telomerase and Cancer Spread (Metastasis)supporting
confidence: 68%
“…Melittin was reported to be involved in apoptosis of human carcinoma cells by activating CaMKII-TAK1-JNK/p38 and inhibiting IkBa kinase-NF-kB pathways (14). Evidence indicates that melittin is a potent cytolytic toxin for tumor cells via in vitro-and in vivotargeted tumor lysis (15,16). In addition, melittin suppresses VEGF-A-induced tumor growth by blocking VEGFR-2 and the COX-2-mediated MAPK signaling pathway in lung cancer cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…It induces membrane permeabilization and lyses prokaryotic and eukaryotic cells in a non-selective manner (Papo and Shai, 2003). This mechanism of action is responsible for the haemolytic, anti-microbial (Blondelle and Houghten, 1991;Bechinger, 1997;Diaz-Achirica et al 1998;Chicharro et al 2001;Luque-Ortega et al 2003;Pérez-Cordero, 2011) andanti-tumour (Li et al 2006;Holle et al 2009) activities of melittin.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism of action is responsible for the haemolytic, anti-microbial (Blondelle and Houghten, 1991; Bechinger, 1997; Diaz-Achirica et al 1998; Chicharro et al 2001; Luque-Ortega et al . 2003; Pérez-Cordero, 2011) and anti-tumour (Li et al 2006; Holle et al 2009) activities of melittin.…”
Section: Introductionmentioning
confidence: 99%